2019
DOI: 10.1111/ans.15016
|View full text |Cite
|
Sign up to set email alerts
|

National trends in surgical therapy for benign prostatic hyperplasia in Australia

Abstract: Key words benign prostatic hyperplasia, national trends, photo-selective vaporization of prostate, surgical therapy, transurethral resection of prostate, UroLift. Correspondence AbstractBackground: To determine national trends in the utilization of surgical procedures for the treatment of benign prostatic hyperplasia (BPH) in Australia over the last 20 years. Methods: The Medicare Australia and Australian Institute of Health and Welfare databases were used to determine the annual number of surgical procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Since the turn of the millennium, there has been significant change in the management of BPH in Australia. The data presented here provides a contemporary analysis of BPH surgery and contribution to national hospitalisations [22], with population-adjustment and analysis of trends in BPH medical therapy and financial burden. These data demonstrated that the overall rate of all BPH procedures rose by 39% across the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Since the turn of the millennium, there has been significant change in the management of BPH in Australia. The data presented here provides a contemporary analysis of BPH surgery and contribution to national hospitalisations [22], with population-adjustment and analysis of trends in BPH medical therapy and financial burden. These data demonstrated that the overall rate of all BPH procedures rose by 39% across the study period.…”
Section: Discussionmentioning
confidence: 99%
“…This dropped to 73% from 2008 to 2014. In 2014 to 2017, 15.5% of procedures were PVP and 7.7% and 5.9% were UroLift® and HoLEP, respectively [91]. A similar decline in the rate of TURP was seen in America with a drop of 47.6% from 2000 to 2008, in favor of PVP, TUNA, and TUMT [92].…”
Section: Newer Therapies For Bphmentioning
confidence: 96%
“…In low‐ and middle‐income countries (most of the world's population), even a bipolar electrocautery may present an investment that is not achievable. The need for a high‐power laser generator, laser fibres, and morcellators is an obstacle to the popularity of aEEP (Jeon et al., 2019; Naspro et al., 2017; Patel & Bariol, 2019).…”
Section: Multiple Energy Sources and Techniquesmentioning
confidence: 99%